INSTITUTIONAL TRIAL OF MINORS CONDEMNED: INTERNATIONAL EXPERIENCE - Artyom Y. Nesterov (Scientific Journal of Pedagogy and Economics, 2020)
The article presents the international positive experience of the probation service for juvenile convicts in the post-prison period, orienting the convict in the process of social adaptation to independent development. An individual who cares about his family and close relatives, benefits the state and society through labor, is a law-abiding citizen who meets all the requirements and generally accepted principles of a legal, modern society and sovereign state. The author of the article formulates the main conclusions, which determine that the main goal of “probation services” is to promote the successful social adaptation of persons of juvenile convicts released from prison. First of all, this assistance consists in rendering assistance to a juvenile convicted person in restoring socially useful ties, social welfare, employment, providing psychosocial, qualified legal and medical assistance, as well as preventing their recidivism. The good practice of the Probation Service of such sovereign states of the World as the Republic of Kazakhstan, Finland, France, Germany, Sweden, Switzerland and Japan is presented.